2010
DOI: 10.1007/s11695-010-0079-1
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Genetic and Metabolic Syndrome to Omental Adipose Tissue PAI-1 Gene mRNA and Plasma Levels in Obesity

Abstract: These results suggest that PAI-1 polymorphisms contribute significantly to PAI-1 plasma levels but do not support the notion that omental AT is one of its major source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…These results obtained in our study are similar to those reported in a previous study done in Caucasian population in which A/A genotype was associated with the susceptibility of developing MetS (OR, 4.87; p < 0.001) [12]. These consistent results reported in different populations may be due to the effect of the polymorphism on the levels of the protein, since it has been reported that the base change of G to A at position -844 of the promoter PAI-1 gene generates a binding site consensus sequence for Ets nuclear protein, which could be involved in regulating gene expression and influencing the increase in PAI-1 plasma protein levels [32,33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results obtained in our study are similar to those reported in a previous study done in Caucasian population in which A/A genotype was associated with the susceptibility of developing MetS (OR, 4.87; p < 0.001) [12]. These consistent results reported in different populations may be due to the effect of the polymorphism on the levels of the protein, since it has been reported that the base change of G to A at position -844 of the promoter PAI-1 gene generates a binding site consensus sequence for Ets nuclear protein, which could be involved in regulating gene expression and influencing the increase in PAI-1 plasma protein levels [32,33].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the -844 G/A polymorphism we observed that is distributed inversely to those reported in Caucasian populations, in which the A allele is more frequent than the G allele [12,18,19]. In our study this polymorphism had a high frequency of G allele and a lower frequency of A allele, consistent with already reported frequencies in previous studies in Mexican mestizo population [20,30], suggesting that in the Mexican population there is a high frequency of allele G.…”
Section: Discussionmentioning
confidence: 56%
“…We also did not find a relationship between the expression of fibrinolytic regulators in adipose tissue and BMI. This finding is in agreement with the study by Bouchard [18], but not with the findings of Alessi [8]. The differences between patients with and without DM could not be confirmed in our study due the small sample size, although it has been reported that hyperglycemia can lead to the increased expression of PAI-1 in adipose tissue [19].…”
Section: Fibrinolytic System Components In Peritoneal Membrane and Thsupporting
confidence: 80%
“…Profibrotic factor TGF-β is also produced by mesothelial cells influenced by peritoneal dialysis fluids [18]. TGF-α, IL-6 and TGF-β are known as modulators of PAI-1 expression.…”
Section: Inflammatory Products Of Adipocytesmentioning
confidence: 99%
“…There are different PAI-1 polymorphisms of clinical importance described previously by various researchers. The most commonly described ones are the following: PAI-1 (rs1799889) -675 4G/5G insertion/deletion polymorphism at -675 in the promoter region [ 10 ], G-A substitution at position -844 (rs2227631) [ 11 , 12 ], c.43G<A (p.A15T, rs6092), and (p.I17V, rs 6090) [ 13 ]. It has been stated that different polymorphisms result in different levels of PAI-1 concentrations.…”
Section: Introductionmentioning
confidence: 99%